The Correlations Between Group Dynamics and Champions' Achievements at Simantri Gapoktan in Bali Province. - M. F., Al Azhah; Suparta, N.; Suarta, G. (Jurnal Peternakan Tropika; Vol 7 No 3 (2019): Issue 7 No. 3 - 2019; September - December 2019, 2019)
In an effort to realize farmer as quality main actors, farmers are directed to develop their abilities through group approaches, learning classes, cooperation vehicles, production units, production infrastructure providers, processing and marketing units, and service units support so that it isto increase the ability of its members in developing agribusiness-based farming, which in turn can become a strong and independent farmer institution. The purpose of this study was to determine the dynamics of Gapoktan Simantri who were champions and not champions in Bali Province. Knowing the correlations between group dynamics and champions' achievements at Simantri Gapoktan in Bali Province.Knowing the right extension system to improve group dynamics at the Simantri Gapoktan in Bali Province. The number of samples used as many as 60 people consisted of 30 groups of champions and 30 groups of non-champions. Research data collection conducted by interview method. The results of the study showed: (1) That the level of dynamics of Gapoktan Simantri which won the championship in Bali Province was more dynamic compared to the dynamics of Gapoktan non champions. (2) There is a very real relationship between the level of dynamism of the Simantri Gapoktan and their achievements. (3) To improve the extension system in Simantri Gapoktan in Bali Province, a counseling system with a method based on a group approach is needed. Farmers or ranchers are guided and directed in groups to do something more productive on the basis of cooperation.   Keywords: Group Dynamics, Simantri Gapoktan, Achievements.